The Impact of divorce on the main male character, Steve Miller, as reflected in Nicholas Sparks’s the last song - Kusumaningrum, Nur Fitrah (COMMICAST, 2021)
The Last Song written by Nicholas Sparks is a novel that tells about family conflict that begins from the divorce between the parents and involves their children. The children must face the reality about their parents’ divorce when they are at the age of ten and seventeen. Not only for their children, but the divorce also brings an impact to the main male character, Steve Miller, in this novel. There is misunderstanding at the beginning in children’s comprehension about the causes of the divorce in their family. But after they know, especially the daughter, everything has changed between the main male character and his children. The aims of this study are to analyze the cause of the divorce and the impact of divorce on male male character, Steve Miller, as reflected in Nicholas Sparks’s The Last Song. The writer uses psychological approach to analyse the cause and the impact of the divorce on the main male character, Steve Miller, as reflected in Nicholas Sparks’s The Last Song. The writer also uses qualitative research method. The primary data are taken from the copy of novel The Last Song (2010) in the form quotation, phrase, and clauses or in the form of sentences that are related to the points discussed in this research. While, the secondary data are taken from all the analysis and criticism related to the novel. This secondary data of this research are also taken from some library documents and internet sources. The result of this study shows that the cause of the divorce in Nicholas Sparks’s The Last Song is because the male main character’s wife had affair with the stranger that he does not know before. It makes the communication with his wife is rarely done. It also involves their children and makes the relationship between father and daughter is broken. Not only to the relationship between the family members, but this divorce also give effects to the main character’s psychological and physical states.